2015
DOI: 10.1134/s1063782615070039
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure of TlFeS2 and TlFeSe2 chalcogenides

Abstract: The crystal and magnetic structures of TlFeS 2 and TlFeSe 2 chalcogenides are studied by neutron diffraction in the temperature range 10-300 K. The investigated compounds feature monoclinic crystal sym metry with the C2/m space group. Antiferromagnetic ordering occurs in TlFeS 2 and TlFeSe 2 at the Néel tem perature T N = 210(5) and 295(5) K, respectively. The temperature dependences of magnetic moments, Fe-Fe bond lengths, and unit cell volume are established. The coefficients of thermal expansion for the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…[13] All AFeX 2 compounds have tetrahedrally co-arXiv:1905.03318v1 [cond-mat.mtrl-sci] 8 May 2019 ordinated Fe 3+ chains along c, but many of these have an additional degree of structural freedom, manifested as a monoclinic distortion (TlFeS 2 , TlFeSe 2 , KFeSe 2 , and RbFeSe 2 with the magnetic moments ordered perpendicular to the chains; and KFeS 2 , RbFeS 2 with the ordered moments slightly tilted from the chain axis). [14,15] Only CsFeS 2 is orthorhombic, but it further distorts martensitically at its magnetic transition at 70 K, with moments slightly tilted off the chain direction. [16] Unlike the well-studied AFeX 2 -type compounds, the compounds in the A 2 M X 2 family have not been examined in sufficient detail to understand any of their magnetic ground states.…”
Section: Introductionmentioning
confidence: 99%
“…[13] All AFeX 2 compounds have tetrahedrally co-arXiv:1905.03318v1 [cond-mat.mtrl-sci] 8 May 2019 ordinated Fe 3+ chains along c, but many of these have an additional degree of structural freedom, manifested as a monoclinic distortion (TlFeS 2 , TlFeSe 2 , KFeSe 2 , and RbFeSe 2 with the magnetic moments ordered perpendicular to the chains; and KFeS 2 , RbFeS 2 with the ordered moments slightly tilted from the chain axis). [14,15] Only CsFeS 2 is orthorhombic, but it further distorts martensitically at its magnetic transition at 70 K, with moments slightly tilted off the chain direction. [16] Unlike the well-studied AFeX 2 -type compounds, the compounds in the A 2 M X 2 family have not been examined in sufficient detail to understand any of their magnetic ground states.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by this theoretical study, we are interested in the ternary 𝐴FeSe 2 and related compounds. A literature survey shown that the layered tetragonal structure used in the above theoretical study [10] is thermodynamically unstable for these 𝐴FeSe 2 compounds, which actually crystallize in the quasi-onedimensional (Q1D) monoclinic structures with space group 𝐶2/𝑐 for 𝐴 = K and Rb [11] and 𝐶2/𝑚 for 𝐴 = Tl, [12] respectively. In the present study, we focus on TlFeSe 2 because it is the only one among these 𝐴FeSe 2 compounds that has been reported to adopt the layered tetragonal structure [13] in addition to the stable monoclinic structure.…”
mentioning
confidence: 99%
“…In this context, the ternary metal chalcogenides AFeX 2 (A=alkali metal, Tl; X=S,Se) are interesting materials because they host linear spin chains formed by edgesharing 1 ∞ [FeX 4/2 ] − tetrahedra along the chain axis, as shown in Fig. 1 (a) [12][13][14] . As previously reported, KFeS 2 , RbFeS 2 , KFeSe 2 , and RbFeSe 2 crystallize in the monoclinic space group C/2c, while TlFeS 2 and TlFeSe 2 crystallize in the monoclinic space group C/2m [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%